Assimilating Immigrants: The Impact of an Integration Program - Matti Sarvimaki; Kari Hamalainen (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Immigration policy design is an important and controversial topic in most developed countries. We inform this debate by evaluating the effects of an integration program for immigrants to Finland. The program consists of an individualized sequence of training and subsidized employment. Non-compliance is sanctioned by reductions in welfare benefits. Our empirical strategy exploits a discontinuity that made participation obligatory in May 1999 only for those who had entered the population register after May 1997. The results suggest that the program strongly increased the employment and earnings of immigrants and reduced their dependency on social benefits.
Keywords: J61; J68; H53; I38; 330; Immigrants; assimilation; integration programs; regression-discontinuity